Texts, Contexts, Intertexts - Rentzsch, Julian,Kučera, Petr (Ergon – ein Verlag in der Nomos Verlagsgesellschaft, 2022)
Dieser Sammelband enthält achtzehn Beiträge zum Werk Orhan Pamuks, eines der führenden Autoren der türkischen Gegenwartsliteratur. Wissenschaftlerinnen und Wissenschaftler mit Wirkungsstätte in der Türkei, in West- und Mitteleuropa und in den USA erörtern verschiedene Fragestellungen seines literarischen Schaffens, darunter Erzähltechnik, seine Verarbeitung historischer, gesellschaftlicher, politischer und kultureller Phänomene, Aspekte der Intertextualität und Intermedialität, Genre-Fragen und Fragestellungen der Rezeption in verschiedenen Ländern. Die akademischen Beiträge in englischer Sprache bieten einer literaturwissenschaftlich interessierten internationalen Leserschaft neue Einsichten und Zugänge zu Pamuks Werk. Mit Beiträgen von Fatih Altuğ , Zeynep Arıkan Yılmaz, Gunvald Axner Ims, Esra Canpalat, Johanna Chovanec, Sylwia Filipowska, Erdağ Göknar, Sibel Irzık, Hasan Bulent Kahraman, Halim Kara, Piotr Kawulok, Erol Köroğlu, Petr Kučera, Aysel Özdilek, Julian Rentzsch, Monika Schmitz-Emans, Zeynep Tüfekçioğlu-Yanaşmayan, Zeynep Uysal und Simge Yılmaz. This volume contains eighteen academic contributions examining the work of Orhan Pamuk, one of the leading authors of contemporary Turkish literature. Scholars working in Turkey, Central and Northern Europe, and the USA discuss various issues of his fictional and non-fictional texts, such as narrative technique, his treatment of historical, social, political, and cultural phenomena, aspects of intertextuality and intermediality, questions of genre as well as the reception of his work in different societies. As the number of academic studies on Pamuk in English is still relatively limited, this book will provide an international readership with an academic interest in literature with new insights and approaches to his work. With contributions by Fatih Altuğ , Zeynep Arıkan Yılmaz, Gunvald Axner Ims, Esra Canpalat, Johanna Chovanec, Sylwia Filipowska, Erdağ Göknar, Sibel Irzık, Hasan Bulent Kahraman, Halim Kara, Piotr Kawulok, Erol Köroğlu, Petr Kučera, Aysel Özdilek, Julian Rentzsch, Monika Schmitz-Emans, Zeynep Tüfekçioğlu-Yanaşmayan, Zeynep Uysal and Simge Yılmaz.
urn:nbn:de:bsz:31-epflicht-2080038
Keywords: Türkei; türkische Literatur; Pamuk; Orhan; Weltliteratur; Orhan Pamuks Politics; Orhan Pamuks Poetics; Orhan Pamuk in the German-Speaking Publishing Market; Intertextuality of Orhan Pamuk; Pictures of Istanbul; Istanbul and the Politics of Memory